Strength and Inter-Relationship of Different Body Parameters of Obesity in Our Local Racial and Ethnic Background (Medical Forum Monthly, 2021)
Objective: By defining the strength of each parameter of obesity in our population as a source of local data for comparison with other ethnic and racial groups, we can focusing on the best parameter of obesity in our routine clinical workup for CVD risk.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Rai Medical College Sargodha and Private Consultancies of the participants from January, 2020 to December, 2020.Materials and Methods: After informed consent and applying inclusion/exclusion criteria, all obese looking or having a sagging or protuberant tummy, 20-70 years old, were evaluated for different parameters of obesity as per standard practices.Results: Out of 928 eligible participant 344 (37.07%) were males and 584 (62.93%) were females. Only 4 (0.07%) female weighed below the IBW. 12 (2.05%) females and 40 (11.63%) male had WC below the respective cut off values. When assessed by W: HtR, only 16 (4.65%) males were below the cut off value. When evaluated by W: HR, 12 (2.05%) females and 16 (4.65%) males were below the cut off values. On BMI scale 16 (4.65%) females and 42 (8.9%) males fell in the healthy range between 18-25. 120 (20.555) females and 130 (23.97%) male were in the borderline range of 26-30. 120 (32.255) females and 80 (23.25%) males were in the low risk range of 31-35. 136 (23.29%) females and 42 (15.11%) males were in medium risk range of 36-40. 112 (19.18%) females and 20 (5.18%) males were in the high risk range of 40 and above.Conclusion: All the parameters of obesity, WC, W: HtR and W: HR, have their limitations. BMI unexpectedly turned out to miss out the most. This can be explained by the fact that all these parameters including most practiced BMI were designed to stratify the CVD and DM risk not the obesity per se. IBW still is the best parameter to define obesity. This study shall lead to further and larger multicenter studies to develop better understanding of anthpometric parameters for our own population.